Pengembangan Game Edukasi Berbasis Android sebagai Media Pembelajaran Berorientasi pada Kemampuan Berpikir Kritis - Syamsi Damarjati; Asih Miatun (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aimed to develop a valid and practical learning media in terms of theory and practice. The learning media expected to be effective to improve students critical thinking ability in linear program of two-variable material. This study uses the Research and Development (R and D) method starting from potential and problem discovery, data collection, product design, design validation, design revision, limited trial, product revision, wider trial, product revision and mass production. However, due to time constrains this research was only carried out until a wilder trial stage. The subjectin this research were students of class X AV in SMK N 39 Jakarta. The data analysis in this study is qualitative descriptive analysis. The results showed that the educational game "Petualangan Program Linier" is valid as a learning media. The result showed that the media validation got 83.91%. Then the game is valid to be practical in terms of theory and practical aspects. Based on the results of the feasibility test, theory ascpect in  this game got 89.44%. And for the assessment of practical aspects that were assessed based on the satisfaction of student responses, they got 82.61%. The game "Petualangan Program Linier" is effective for practicing  students critical thinking ability. This is evidenced by student learning outcomes which were assessed based on indicators of critical thinking ability. The results showed that 78.26% of students were able to achieve the Minimum Completeness Criteria